ANALYSIS OF DEIXIS IN THE COLLECTION OF SHORT STORIES DUSK, RAIN, AND THE STORY THAT NEVER ENDS BY BOY CANDRA - Rosa, Alya Alya (English Edu: Journal of English Teaching and Learning, 2025)
This study investigates the use of deixis in the short story collection Senja, Hujan, dan Kisah yang Tak Kunjung Usai by Boy Candra, focusing on how various types of deictic expressions contribute to narrative construction and emotional depth. Employing a descriptive qualitative approach within the framework of pragmatics, the research identifies and analyzes five categories of deixis: personal, temporal, spatial, discourse, and social. The data were collected through document analysis of two selected stories, where linguistic units containing deictic elements were extracted and interpreted contextually. The findings reveal that personal deixis is the most dominant, with frequent use of first- and second-person pronouns that build a strong emotional connection between the narrator and the reader. Temporal deixis helps in mapping the flow of time and emotional transitions, while spatial deixis evokes memory-laden locations that symbolize emotional states. Discourse deixis maintains textual cohesion and guides the reader through the narrative structure. Although less frequent, social deixis reflects interpersonal relationships through the use of familiar address terms. Overall, the study demonstrates that deixis in Boy Candra’s stories functions not merely as a linguistic device but as a narrative strategy that enhances intimacy, emotional resonance, and narrative coherence. This research contributes to the growing body of literature on literary pragmatics and offers insight into the linguistic artistry embedded in contemporary Indonesian popular fiction. Keywords: Deixis; Pragmatics, Short Story, Boy Candra, Literary Analysis